The acceptance of Islamic JV among microenterprise operators / Rozita @ Uji Mohammed … [et al.] - Mohammed, Rozita @ Uji; Purag, Muraddin; Mohamad, Mohammad Firdaus; Ag Budin, Dg Kamisah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
Most Small Medium Enterprises (SMEs) worldwide operate as microenterprises and quite a significant number inheriting their family businesses. In Malaysia, as reported by Economic Census 2016, majority of the business establishments can be classified as microenterprises (76.5%) followed by small (21.2%) and medium (2.3%). Although their establishments are dominant in number, but their contribution to the economy is still disproportionately low, i.e. only 37.1% of gross domestic product (GDP) and 17.3% of the total export value as reported by SME Corp in 2017. The microenterprise operators primarily engage in cash transactions because they are micro or even tiny in size including what are called as ‘invisible entrepreneurs’ and ‘nano-enterprises’. Thus, they prefer to obtain financing from non-banking channels. Although many SME financing alternatives have been provided by the banking sector, but yet microenterprise operators still prefer informal funding due to their flexibility in terms of documentation, repayment, timing, and transaction costs, which formal banking and financial institutions are very rigid about it. The researchers conducted a pilot study on microenterprise operators running businesses in Kota Kinabalu City Centre (KKCC) in order to seek their acceptance towards the Islamic JV concept. Many scholars believe the nearer the enterprise to the bank i.e. within 5 kilometres radius, the higher the opportunity for JV to be materialized between operators and banks. Furthermore, microenterprises are said to groom big from micro to small and to medium if operators opened their door for Islamic JV which is based on actual profit generated from the venture where all parties involved as active partners. Hence, the objective of this research is to determine the acceptance of microenterprise operators towards the Islamic JV concept. This study also identifies possible banking factors that could be considered affecting their acceptance. Based on the result, the Islamic JV is said to be moderately accepted by the microenterprise operators located in the KKCC. However, their level of acceptance could have been higher if they had a better understanding of the terms used, the operations applied, the PLS principles and the risk factors. Five major banking factors contributed towards their understanding comprise profit-loss-sharing (PLS) principle, Islamic JV design, accept if understand (from the awareness effort made by the banking sector), reputation and image of the particular bank, and knowledgeable and trained banking personnel.